Marriage Dispensation in Early-Age Marriages and Its Impact on Divorce Rates at the Jember Religious Court - Ashari, Beni (FALASIFA : Jurnal Studi Keislaman, 2024)
Early-age marriage remains a common social phenomenon in Indonesia, including in Jember Regency. Many families apply for marriage dispensation at the religious court as a solution to avoid premarital pregnancy or due to other social factors, despite the legal minimum age of 19 for marriage. This study aims to examine how judges at the Jember Religious Court grant marriage dispensation to underage applicants and whether the high number of dispensation requests correlates with the rising divorce rate. This research is a field study using a normative-juridical approach and descriptive qualitative method. Primary data were obtained through interviews with judges at the Jember Religious Court, while secondary data were collected from relevant literature such as books, journals, and legal documents. The findings reveal that judges only process marriage dispensation requests if the applicant is at least 18 years old, in accordance with agreements between the local government, health agencies, psychologists, P3KB, BKKBN, and other relevant institutions. Dispensations for applicants under 18 are only granted if supported by medical recommendations. Furthermore, judges emphasized that the increase in divorce rates is not solely caused by marriage dispensations but also by emotional immaturity and stunting. Therefore, education for parents and prospective couples on the emotional, legal, and social risks of early marriage is crucial to reduce divorce rates.